Effect of water-deficit on stem reserve mobilization for grain filling in wheat (Triticum aestivum L.) - Kaur, Kulveer; Ghai, Navita; Kaur, Satinder; Singh, Satinder; Sharma, Achla (Journal of Cereal Research, 2024)
The grain filling and development is considered as a key step for wheat yield and is most sensitive to water-deficit. In order to understand the effect of water-soluble carbohydrates (WSC) accumulation and mobilization on water-deficit tolerance, wheat lines viz., check PBW725, parent DS5Ut(5A) and introgression lines (ILs) (5U-24, 5U-26, 5U-27 and 5U-31) were used in this experiment. We examined the pattern of accumulation and mobilization water-soluble carbohydrates in peduncle (Ped), upper internodes (Uint), middle internodes (Mint) and basal internodes (Bint) under water-deficit. Bint showed highest mobilization WSC reserves for grain filling indicating that the lower portions of the stem may exhibit higher remobilization efficiency under water-deficit conditions. Among the ILs, IL 5U-26 showed highest mobilization of WSC in all the internodes. Correlation analysis depicted that increase in mobilization of WSC from Uint, Mint, Bint and Ped enhanced TGW significantly. Highest significant correlation of percent increase in TGW was found with percent change of WSC in Ped (0.97, significant at p<0.01) Also, defoliation studies were carried out under both irrigated and rain-fed conditions to study the mobilization of stem reserves that can provide essential carbon resources for grain-filling to compensate grain weight under defoliated conditions. TGW was reduced after defoliation with significant minimum reduction in IL 5U-26 under irrigated conditions while with non-significant reduction in IL 5U-26 under rain-fed conditions. Also, IL 5U-26 exhibited maximum increase in stem reserve mobilization (SRM) under rain-fed conditions. This indicated that water-deficit considerably increased the remobilization of stem reserves, which enhanced grain filling and contributed significantly to grain weight in 5U-26. Thus, 5U-26 with improved mobilization efficiency can be used in future breeding programmes to enhance grain filling and ultimately yield in wheat.